Spectacular science, technology and superstition in the age of Shakespeare - Chiari, Sophie; Popelard, Mickaël (Edinburgh University Press, 2017)
To the readers who ask themselves: What is science?', this volume provides an answer from an early modern perspective, whereby science included such various intellectual pursuits as history, poetry, occultism and philosophy.